“We who have wallowed in the mud of Flanders”: First World War Veterans, Unemployment and the Development of Social Welfare in Canada, 1929-1939 - Campbell, Lara (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 2000)
AbstractDuring the Great Depression, First World War veterans built on a history of post-war political activism to play an important role in the expansion of state-sponsored social welfare. Arguing that their wartime sacrifices had not been properly rewarded, veterans claimed that they were entitled to state protection from poverty and unemployment on the home front. The rhetoric of patriotism, courage, sacrifice, and duty created powerful demands for jobs, relief, and adequate pensions that should, veterans argued, be administered as a right of social citizenship and not a form of charity. At the local, provincial, and national political levels, veterans fought for compensation and recognition for their war service, and made their demands for jobs and social security a central part of emerging social policy.